The Employee Dismissal Procedure: Some Issues of Theory and Practice - Stahi, Tatiana; Robea, Mariana (Journal of Danubian Studies and Research, 2023)
The actuality of the research topic is conditioned by the theoretical and practical importance of the subjects related to the institution's understanding of the termination of the individual employment contract and, in particular, the termination of the individual employment contract at the initiative of the employer (dismissal) and the determination of its place and role within labor law, and not only. The institution of labor law, perhaps more than any of the legal institutions, is constantly undergoing a deep transformation, in the context of the new legislative changes in labor law. Obviously, the sub-institution of termination of the individual employment contract at the initiative of the employer is subject to the same development process. Due to this fact, we have devoted ourselves completely to the understandable approach of this institution, trying to elucidate the consequences that appear in the socio-legal level, as a result of the termination of employment relations.